1995
DOI: 10.1136/hrt.74.5.541
|View full text |Cite
|
Sign up to set email alerts
|

Atrial thrombi occurring during sinus rhythm in cardiac amyloidosis: evidence for atrial electromechanical dissociation.

Abstract: Thrombus formation in the left atrium is rare in patients in sinus rhythm. In three patients with extensive cardiac amyloidosis transthoracic echocardiography showed large atrial thrombi in or protruding into the body of the left atrium during sinus rhythm. Doppler studies showed no A wave on mitral inflow. Severe atrial and ventricular infiltration by amyloid may have resulted in mechanical atrial standstill with resultant thrombus formation. These findings suggest that patients with severe cardiac amyloidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 15 publications
4
71
2
7
Order By: Relevance
“…LV diastolic dysfunction and low LAA emptying velocity, in addition to AF, were independently associated with intracardiac thrombosis. The Mayo autopsy and TEE studies and prior study support the hypothesis that the combination of systolic and diastolic ventricular dysfunction and chronic amyloid infiltrate in the atria lead to atrial mechanical dysfunction, 17,24 atrial enlargement, and blood stasis. 23,27 Such atrial electrical-mechanical dissociation at least partially explains why some cardiac amyloid patients developed atrial thrombosis while in sinus rhythm.…”
Section: Tte Tee Characters and Intracardiac Thrombosissupporting
confidence: 48%
See 4 more Smart Citations
“…LV diastolic dysfunction and low LAA emptying velocity, in addition to AF, were independently associated with intracardiac thrombosis. The Mayo autopsy and TEE studies and prior study support the hypothesis that the combination of systolic and diastolic ventricular dysfunction and chronic amyloid infiltrate in the atria lead to atrial mechanical dysfunction, 17,24 atrial enlargement, and blood stasis. 23,27 Such atrial electrical-mechanical dissociation at least partially explains why some cardiac amyloid patients developed atrial thrombosis while in sinus rhythm.…”
Section: Tte Tee Characters and Intracardiac Thrombosissupporting
confidence: 48%
“…Furthermore, the LV diastolic function and atrial mechanical activity were more impaired. Reduced atrial contractility secondary to amyloid infiltration has been reported 17,24 and LV diastolic function is typically impaired before systolic function. 25 The combination of systolic and diastolic ventricular dysfunction, chronic amyloid infiltrate in the atria, and direct toxic effect on myocardium 26 could lead to atrial mechanical dysfunction, atrial enlargement, and blood stasis.…”
Section: Mechanism For Thromboembolismmentioning
confidence: 99%
See 3 more Smart Citations